The less healthy urban population: income-related health inequality in China - Yang Wei; Kanavos Panos (BMC, 2012)
Abstract Background Health inequality has been recognized as a problem all over the world. In China, the poor usually have less access to healthcare than the better-off, despite having higher levels of need. Since the proportion of the Chinese population living in urban areas increased tremendously with the urbanization movements, attention has been paid to the association between urban/rural residence and population health. It is important to understand the variation in health across income groups, and in particular to take into account the effects of urban/rural residence on the degree of income-related health inequalities. Methods This paper empirically assesses the magnitude of rural/urban disparities in income-related adult health status, i.e., self-assessed health (SAH) and physical activity limitation, using Concentration Indices. It then uses decomposition methods to unravel the causes of inequalities and their variations across urban and rural populations. Data from the China Health and Nutrition Survey (CHNS) 2006 are used. Results The study finds that the poor are less likely to report their health status as "excellent or good" and are more likely to have physical activity limitation. Such inequality is more pronounced for the urban population than for the rural population. Results from the decomposition analysis suggest that, for the urban population, 76.47 per cent to 79.07 per cent of inequalities are driven by non-demographic/socioeconomic-related factors, among which income, job status and educational level are the most important factors. For the rural population, 48.19 per cent to 77.78 per cent of inequalities are driven by non-demographic factors. Income and educational attainment appear to have a prominent influence on inequality. Conclusion The findings suggest that policy targeting the poor, especially the urban poor, is needed in order to reduce health inequality.